Ultrasonic songs and stridulum anatomy of Asiophlugis crystal predatory katydids (Tettigonioidea: Meconematinae: Phlugidini). Issue 6 (1st November 2020) - Tan, Ming Kai; Montealegre-Z, Fernando; Bin Haji Abdul Wahab, Rodzay; Lee, Chow-Yang; Belabut, Daicus; Japir, Razy; Chung, Arthur
ABSTRACT: The behavioural ecology of ultrasonic-singing katydids is not well understood, and the general bioacoustics, barely known for a few Neotropical Meconematinae, tends to be overlooked for species from Southeast Asia. These include Asiatic species of Phlugidini, commonly known as crystal predatory katydids. One of its genera, Asiophlugis consists of 16 species for which acoustic signals and stridulum anatomy are broadly unknown. These characters can be used to understand species boundaries. Here, we sampled Asiophlugis from five sites in Malay Peninsula and Borneo Island, recorded the acoustic signals of five species plus one subspecies using ultrasound sensitive equipment, and examined their stridulum anatomy. The calling songs of the taxa involved were documented for the first time. We found that the stridulum anatomy (e.g., tooth distributions, tooth length and tooth density) is distinct between species but less so between subspecies. In contrary, songs of different taxa are different based on acoustic parameters (e.g., pulse duration, peak frequency) and descriptive patterns, even between the subspecies. We also did not observe that song signals are more different in sympatry than in allopatry. Whether this can be generalised requires further sampling, highlighting the need for more research on the ultrasonic acoustic communication in Asiatic katydids.